Football Performance Test - Vincenzo Alberto Annese; Tandiyo Rahayu; Soegiyanto MS; Donny Wira Yudha Kusuma (International Conference on Science, Education, and Technology, 2022)
This research on the professional football coach competency evaluation instrument was done because there was no existing instrument used to measure the test to select players’ competence in India (female and male). Subjects in this study, 18 male and 18 female players from India from a professional sports club were involved respectively. The physical characteristics of the participants are shown in this experimental study. The players performed a battery of four tests during normal weekly training. The research was in the period between January and March 2022 in quantitative method research. Motor capacity in detail, the speed was analyzed with a 20 m Sprint, the strength with a counter-movement without using the arms (CMJ), the resistance with the "YoYo Intermittent Recovery Test - Level 1 "(YYIR1),” and coordination with a test characterized by running, slalom with the ball, jumping of the obstacle 20 meters plus 20 meters. Before each, the protocol was explained and the correct technique was demonstrated; the speed, endurance, and coordination tests. We can illustrate this research as the use of standardized tests for twelve with execution in the first two days of the week of the typical week preceding the game. This study leads to the awareness that the various tests carried out repeatedly over time can be useful if stimulated adequately for the continuous improvement of performance and therefore not only used for the purpose to understand the physical qualities of individual players.